Development of a hyper-adhesive and attenuated Edwardsiella ictaluri strain as a novel immersion vaccine candidate in yellow catfish (Pelteobagrus fulvidraco). (June 2022) - Liu, Ying Li; He, Tian Tian; Jiang, Xiu Long; Sun, Shan Shan; Wang, Long Kun; Nie, Pin; Xie, Hai Xia
Abstract: Edwardsiella ictaluri, a Gram-negative intracellular pathogen, is the causative agent of enteric septicemia in channel catfish, and catfish aquaculture in China suffers heavy economic losses due to E. ictaluri infection. Vaccination is an effective control measure for this disease. In this study, an attenuated E. ictaluri strain was acquired through deletion mutation of the T3SS protein eseJ ei, and the Δ eseJ ei strain fails to replicate in the epithelioma papillosum of carp cells. The type 1 fimbria plays a pivotal role in the adhesion of E. ictaluri, and it was found in this study that deletion of −245 to −50 nt upstream of fimA increases its adhesion to around five times that of the WT strain. A hyper-adhesive and highly attenuated double mutant (Δ eseJ ei Δ fimA -245 --50 strain) was constructed, and it was used as a vaccine candidate in yellow catfish via bath immersion at a dosage of 1 × 10 5  CFU/mL. It was found that this vaccine candidate can stimulate protection when challenged with E. ictaluri HSN-1 at 5 × 10 7  CFU/mL (∼20 × LD50 ). The survival rate was 83.61% for the vaccinated group and 33.33% for the sham-vaccinated group. The RPS (relative percent of survival) of the vaccination trial reached 75.41%. In conclusion, the Δ eseJ ei Δ fimA -245 --50 strain developed in this study can be used as a vaccine candidate. It excels in terms of ease of delivery (via bath immersion) and is highly efficient in stimulating protection against E. ictaluri infection. Highlights: Deletion of T3SS effector eseJ ei abolishes replication of E. ictaluri HSN-1 in the Epithelioma papillosum of carp (Cyprinus carpio) cells. Deletion of −245 to −50 nt upstream of fimA increases its adhesion to around five times that of the wild-type strain. Double deletion mutant strain Δ eseJ ei Δ fimA -245 --50 is highly attenuated and hyper-adhesive. The relative percent of survival reached 75.41% when yellow catfish were vaccinated with Δ eseJei Δ fimA -245 --50  strain.